Ureteral tunnel length versus ureteral orifice configuration in the determination of ureterovesical junction competence: A computer simulation model. Issue 3 (June 2018) - Villanueva, C.A.; Tong, J.; Nelson, C.; Gu, L.
Summary: Introduction: The long-held belief that a ureteral re-implant tunnel should be five times the diameter of the ureter, as proposed by Paquin in 1959, ignores the effect of the orifice on the occurrence of reflux. In 1969, Lyon proposed that the shape of the ureteral orifice (UO) is more important than the intravesical tunnel. However, both theories missed quantitative evidence from principles of physics. The goal of the current study was to test Lyon's theory through numerical models (i.e. to quantify the sensitivity of ureterovesical junction (UVJ) competence to intravesical tunnel length and to the UO). Materials and methods: The closure of a three-dimensional spatial configuration of ureter, constrained within a bladder, was simulated. Two common UO shapes (i.e. golf type vs 2-mm volcano type (Summary Fig.)), and two different intravesical ureteral tunnel length/diameter ratios (3:1 and 5:1) were examined. The required closure pressures were then compared. Results: The UO was a significant factor in determining closure pressure. Given the same intravesical ureteral tunnel length/diameter ratio, the required closure pressure for the volcanic orifice was 78% less than that for the golf orifice. On the other hand, the intravesical ureteral tunnel length/diameter ratio had minimal effect on the required closure pressure. As the intravesical ureteral tunnel length/diameter ratio changed from 3:1 to 5:1, the required closure pressure was reduced by less than 7%, regardless of the orifice shape. Conclusions: The simulation results showed that UVJ competence was more sensitive to a 2-mm protrusion of the UO compared to an increase in the intravesical tunnel length from 3:1 to 5:1. This agrees with Lyon's theory, and at the same time challenges Paquin's 5:1 rule. Researchers could use this information to consider the UO configuration in further animal, human, computer or material models. Summary Figure Forces affecting a golf-type versus volcanic-type ureteral orifice.